GUN: Representations of North American Myths and Stereotypes in the Controversial 2005 Western - Angel Todorov, (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2025)
This article explores the intersections between video games and American myths and minority stereotypes. It specifically focuses on the 2005 game GUN and its relation with co-representatives of the western genre, Assassin’s Creed III and the Red Dead Redemption series. It analyses and compares the narratives of the games in question, as well as key gameplay elements within. The study reveals a myriad of similarities in the stereotypical topics covered, as well as crucial differences in how certain aspects of Native American portrayal were handled by the developer teams. GUN included an orphaned, mixed-ethnicity protagonist prior to Assassin’s Creed III, a gunslinger who looks and shoots very similarly to the main character of Red Dead Redemption, among other notable correlations. Crucially distinctive was the inclusion of player-controlled scalping as the pinnacle of Native American dehumanization in GUN, in addition to other violent tropes limiting the identity of those characters to one that is only associated with combat. This study shows how GUN featured potential-laden ideas, yet its conclusion is that the game ultimately perpetuates the common fallacies of the western genre, rather than make a genuine attempt at deconstructing them.